Diseño e implementación de un sistema de control de movimiento con actuador hidráulico para simulador de terremotos a escala sobre una máquina centrifuga (2010)
This article presents the non-linear mathematical model of a one degree of freedom electro-hydraulic shaking table for simulating earthquakes in soil scale models that are influenced by a centrifugal force. The problem presents three challenges: The first one is that when a body is exposed to a certain centrifugal force to simulate gravity on it, so the time and the magnitude of the displacement should be divided by the number of gravity (N) that is being applying to get a model N times bigger; the second one is that the friction in the servo valves Will increased and that the system require a high bandwidth. The model is used to design three techniques of feedback control: Linear Quadratic Gaussian with loop transfer recovery (LQG-LTR), feedback linearization and Model Predictive Control. Simulations with the non-linear model are presented for the earthquakes of Umbria Italia in 29-04-1984, Mammoth Lakes - Aftershock U.SA in 26-05-1980 and Mexico in 19-09-1985. To implements these techniques there are presented the architecture of the software which was implemented in a embedded computer of National Instruments. This control is commanded from a personal computer by Ethernet network. After there is presented a "black box" model which is obtained using a closed loop algorithm (CLOE) because the system is unstable in open loop for the reason that it has an integrator and it also presents a span problem of the servo valve that does not allow a zero flow at the output of the valve itself. With this model, the controllers LQG-LTR and Model predictive Control are recalculated to obtain experimental results. Finally, some comparisons Of the models ("black box" and "white box") that let to conclude some future works in the machine design to improve the bandwidth of it and let to show how the parameters in "white box" can be approximated by the "black box".